Język jako narzędzie poznania i komunikacji - Adamska, Krystyna (Acta Universitatis Lodziensis. Folia Psychologica, 2013)
The paper presents arguments for treating language as a tool for cognition and communications. It articulates an opposite view to the one which considers language as an independent module shaping cognition and thinking. According to the conception of the socially – based cognition the mind is a controller of the adaptive behavior, and communication is a strategic action to which language is subjected. The model of the linguistic categories arranges words according to the level of their abstraction; and a number of research results presented in the paper indicate that there is a relationship between the level of abstraction of the words used and the inference related to events, emotions and memory. Recognizing language as a tool for cognition and communication leads to the acceptance of the necessity to widen the language awareness. This kind of thinking is supported by the presented results of research on the relationship between linguistic categories and the stereotypes, communication of the interpersonal distance and the process of asking questions and giving answers.